Предмет: Математика,
автор: mskosmoskseni
Упростить:
-8(k-3)+4(k-2)-2(3k+1)=
5/9*(3.6a-3 3/5в)-3,5*(4/7а-0,2в)
Ответы
Автор ответа:
1
-8(k-3)+4(k-2)-2(3k+1)=-8k+24+4k-8-6k-2=-10k+14
5/9*(3.6a-3 3/5b)-3,5*(4/7a-0,2b)=2a-2b-2a+0.7b=-1.3b
5/9*(3.6a-3 3/5b)-3,5*(4/7a-0,2b)=2a-2b-2a+0.7b=-1.3b
Похожие вопросы
Предмет: Қазақ тiлi,
автор: kats13
Предмет: Русский язык,
автор: Vladisis
Предмет: Английский язык,
автор: vagifona
Предмет: Русский язык,
автор: Aleksandrvoloshin043
Предмет: Математика,
автор: vasilisa484